Heat-treatment effects on the magnetic response of superconducting mesoscopic samples - Motta, M. [UNESP]; Deimling, C. V.; Ortiz, W. A.; Lisboa Filho, Paulo Noronha [UNESP] (Elsevier B.V., 2008)
The use of chemical methods in the synthesis of high-quality and small-size polycrystalline samples has been increased in recent years. In this work, a chemical route based on an aqueous precursor solution of metals followed by the addition of a water-soluble polymer formed by ethylenediaminetetraacetic acid (EDTA) and ethylene glycol (EG) was tested to produce superconducting mesoscopic YBa(2)Cu(3)O(7-gamma) samples. Different conditions of heat treatments and the effects of argon and oxygen atmospheres during the calcination steps were traced using X-ray diffraction (XRD), scanning electron microscopy (SEM) and magnetic measurements. (C) 2008 Elsevier B. V. All rights reserved.
Keywords: superconducting material; heat treatment; YBCO; chemical route